THE CURIOUS CASE OF THE HIDDEN PARATHYROID GLAND: TWO CASE SERIES - MM, Nur Hidayah; MA, Masliza Hanuni; WA, Siti Sanaa (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND The main challenge in managing primary hyperparathyroidism is localization of hyperfunctioning parathyroid gland. This step is crucial prior to parathyroidectomy to ensure effectiveness of surgical treatment and reducing the risk of re-operation. CASE We encountered 2 cases with difficulty in localizing the parathyroid gland. The first case, 34-year-old female, presented with renal colic and noted to have bilateral renal calculi and hypercalcemia (calcium 2.94 mmol/L, phosphate 0.64 mmol/L). The second case, 46-year-old female, presented with body weakness and incidental finding of hypercalcemia (calcium: 2.84 mmol/L, phosphate: 0.52 mmol/L). Both have high serum iPTH of 98.5 pg/ml and 83.9 pg/mL, respectively. Bone mineral density revealed total Z-score of – 0.7 and – 2.1, respectively. Their kidney ultrasound showed bilateral medullary nephrocalcinosis. Both cases were diagnosed with primary hyperparathyroidism. For the first case, initial neck ultrasound and sestamibi scan failed to localize any parathyroid adenoma. FDG-PET scan showed no evidence of uptake elsewhere. CT of the neck with delayed venous phase revealed single nodule seen at the upper border of left thyroid gland. A repeat neck ultrasound showed a single hyperechoic nodule in concordance with findings in the CT of the neck. In the second case, neck ultrasound revealed 2 intrathyroidal lesions at bilateral lower pole of the thyroid gland. Sestamibi scan showed no evidence of hyperfunctioning parathyroid tissue. CT of the neck with delay venous phase revealed similar intrathyroidal nodular lesion seen in the ultrasound. However, no hypodensity was seen in delayed venous phase which was not a suggestive feature of parathyroid adenoma. Left superior parathyroidectomy was planned for the first patient. Meanwhile, an exploratory bilateral inferior neck surgery is scheduled for the second patient. CONCLUSION There are few reasons contributing to a false-negative sestamibi scan. In addition, neck ultrasound is operatordependant. Hence, alternative imaging modalities are important to help with parathyroid gland localization.